Pengendalian Nematoda Meloidogyne spp. pada Tanaman Tomat (Lycopersicon esculentum Mill.) Dengan Gliocladium sp. dalam Media Bokashi Alang-Alang (Imperata cylindrica L.) - Muhammad Nur Himawan; Elly Liestiany; Rahmi Zulhidiani (Universitas Lambung Mangkurat, 2018)
The purpose of this study was to determine the effectiveness and the best dose of Gliocladium sp.in imperata bokashi media, in suppressing the attack of nematode root roots. This research usedRAL research design in one factor polybag media with 6 treatments, 4 replications and 24experimental units. The treatment consists of K). Imperata bokashi (20.8 g) A). Imperatabokashi (20.8 g) + Gliocladium sp. 10 g B). Imperata bokashi (20.8 g) + Gliocladium sp. 15 g C).Imperata bokashi (20.8 g) + Gliocladium sp. 20 g D). imperata bokashi (20.8 g) + Gliocladiumsp. 25 g E). Imperata bokashi (20.8 g) + Gliocladium sp. 30 g. The result of the study showedthat Glocladium sp. in imperata bokashi media have real effect in controlling Meloidogyne sppnematodes. in Tomato plants, significantly affect the growth of Tomato plant height, but nosignificant effect on wet weight and dry weight of plants.